2018
DOI: 10.1186/s13033-018-0180-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving the capacity of community-based workers in Australia to provide initial assistance to Iraqi refugees with mental health problems: an uncontrolled evaluation of a Mental Health Literacy Course

Abstract: BackgroundAustralia is a multicultural nation with a humanitarian program that welcomes a large number of Iraqi refugees. Despite the high prevalence of trauma related disorders, professional help-seeking in this group is very low. This study sought to evaluate a face-to-face mental health literacy (MHL) Course that teaches community-based workers how to provide initial help to Iraqi refugees with depression and post-traumatic stress disorder (PTSD) related problems.MethodsAn uncontrolled pre, post and follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Participants' negative attitudes towards mental illness were assessed using the modified Personal Stigma in Response to Mental Illness Scale [22,25,26]. Personal stigma was assessed by asking participants to respond to nine statements concerning the person described in the vignette using a 5-point Likert-type scale (1: 'strongly agree' to 5: 'strongly disagree').…”
Section: Negative Attitudes Towards Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' negative attitudes towards mental illness were assessed using the modified Personal Stigma in Response to Mental Illness Scale [22,25,26]. Personal stigma was assessed by asking participants to respond to nine statements concerning the person described in the vignette using a 5-point Likert-type scale (1: 'strongly agree' to 5: 'strongly disagree').…”
Section: Negative Attitudes Towards Mental Illnessmentioning
confidence: 99%
“…Social distance was assessed using five statements from the social distance scale developed by Link and colleagues [28], which has also been used in previous research by the authors [22]. Participants were asked to consider whether/ to what extent they would be pleased to spend time with Dawood/Miriam in different situations: 'living next door to Dawood/Miriam' and 'having Dawood/Miriam marry into your family', for example.…”
Section: Negative Attitudes Towards Mental Illnessmentioning
confidence: 99%
“…An uncontrolled evaluation (with measures at pre-, post- and 6-months follow-up) found a number of improvements, including in mental health first aid knowledge, confidence to help and stigma. 63 However, no change in helping behaviours was found over the follow-up period.…”
Section: Resultsmentioning
confidence: 94%
“…Participants' negative attitudes towards those with mental illness were assessed using the modified Personal Stigma in Response to Mental Illness Scale [15,28,31]. Personal stigma was assessed by asking participants to respond to statements concerning the person described in the vignette using a 5-point Likert-type scale (1: 'strongly disagree' to 5: 'strongly agree').…”
Section: Negative Attitudes Towards Mental Illnessmentioning
confidence: 99%
“…Relatedly, research has demonstrated the well-regarded mental health first aid (MHFA) program delivered to culturally diverse groups such as the Chinese and Vietnamese communities in Australia, can lead to improvements in the MHL in these groups following such interventions [13,14]. Spurred on by such successes, a number of MHFA interventions have since been undertaken within refugee populations including the capacity of building community workers to assist refugees with mental health problems [15] and improving the MHL and help-seeking behaviours of teens from culturally diverse backgrounds and the responsible adults who work with them [16].…”
Section: Introductionmentioning
confidence: 99%